Academic Vocabulary of Chilean Textbooks: Analysis of the Words Common to the 4 Core Disciplines of Schooling - Aravena, Soledad (2025)
This study aimed to explore the vocabulary of Chilean textbooks from 4 disciplines and 12 educational levels, analyzing how words are distributed by discipline, school level, degree of polyvalence and disciplinary specialization. From an initial corpus of 2.6 million words, common words to the 4 subjects were extracted to form a list of academic vocabulary. The results indicate that these words increase in frequency at higher levels and are distributed according to the more humanistic or more scientific nature of the subjects and their nature more focused on content or skills. The study concludes by highlighting the importance of examining this vocabulary in order to promote its teaching throughout the entire school trajectory.